Sustaining our future: resolving the conflict over population models - Newman, Peter (The Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
If we are to sustain our future we have to resolve some fundamental issues about how to live on this planet. However underneath it all is a major issue: are there just too many of us? This paper will try to assess the question by looking at two conflicting models that stem from biology and from economics and try to suggest that the conflict can be resolved with new approaches to sustainable cities. It suggests that population issues on a global level need to be addressed as a matter of human rights but fear of population can be a dangerous diversion and prevent cities from grasping the opportunities (provided by growth) to achieve significant urban sustainability gains.